1990
DOI: 10.1128/mcb.10.12.6500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TUP1, a mediator of glucose repression in Saccharomyces cerevisiae.

Abstract: The TUPI and CYC8 (=SSN6) genes of Saccharomyces cerevisiae play a major role in glucose repression. Mutations in either TUPI or CYC8 eliminate or reduce glucose repression of many repressible genes and induce other phenotypes, including flocculence, failure to sporulate, and sterility of MATa cells. The TUP) gene was isolated in a screen for genes that regulate mating type (V. L. MacKay, Methods Enzymol. 101:325-343, 1983). We found that a 3.5-kb restriction fragment was sufficient for complete complementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
170
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 59 publications
4
170
0
1
Order By: Relevance
“…: 415-476-8783; Fax: 415-476-0939. 1 The abbreviations used are: GST, glutathione S-transferase; DTT, dithiothreitol; PAGE, polyacrylamide gel electrophoresis; TBST, Trisbuffered saline plus 5% milk and 0.2% Tween; TPR, tetratricopeptide repeat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…: 415-476-8783; Fax: 415-476-0939. 1 The abbreviations used are: GST, glutathione S-transferase; DTT, dithiothreitol; PAGE, polyacrylamide gel electrophoresis; TBST, Trisbuffered saline plus 5% milk and 0.2% Tween; TPR, tetratricopeptide repeat.…”
Section: Methodsmentioning
confidence: 99%
“…However, an increasing number of WD repeat proteins have been identified that are nuclear localized and function in the repression of transcription. These include Tup1, Hir1, and Met30 in S. cerevisiae; SCON2 in Neurospora crassa; extra sex combs and groucho in Drosophila; COP1 in Arabidopsis thaliana; and HIRA and the family of TLE proteins in humans (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These WD repeat repressor proteins turn off a wide variety of genes, including those involved in segmentation, sex determination, and neurogenesis (controlled by groucho) and those involved in photomorphogenesis (controlled by COP1) (7,11).…”
mentioning
confidence: 99%
“…Glutamine-rich sequences are found in many regulatory proteins and it has been speculated they may mediate interactions between domains (Williams and Trumbly, 1990). The second of these polyglutamine sequences forms part of a repeat of the sequence RIASPIQ.…”
Section: Characterization Of the Tsll Genementioning
confidence: 99%
“…1987;Trumbly. 1988;Williams and Trumbly, 1990), The CYC8 protein contains 10 copies of the 34-amino-acid tetratricopeptide (TPR) repeat near the W-terminus (Sikorski etai, 1990;Hirano et ai. 1990), and these repeats are required for CYC8 function (Schultz etat., 1990).…”
Section: Mechanisms Of Control Of Invertase Expressionmentioning
confidence: 99%